Beyond accessibility: empowering mobility-impaired customers with motivation differentiation. Issue 9 (27th August 2019) - Zhang, Ye; Gao, Jie; Cole, Shu Tian; Ricci, Peter
Abstract : Purpose: To sufficiently fulfill the travel potential of people with mobility impairments (PwMIs), this study aims to propose a valuable supplement to facility/service accommodation by hospitality/tourism businesses by identifying and purposefully cultivating the superior motivation types for empowering PwMI's travel pursuits despite challenges. To this end, the study proposes a self-determined versus controlled motivation subdivision to the predominant travel motivation typologies, with its practical value, theoretical value and application feasibility verified. Design/methodology/approach: To ensure the verification reliability across challenge travels, the study adopts an extreme groups design for data collection. Qualtrics surveys situated in two resort-package scenarios contrast in facility/service accommodation levels are paired with two US PwMI groups contrast in travel capabilities. An unconventional mix of analytical information and seemingly unrelated regressions are adopted for data analyses. Findings: Self-determined motivations are found as the superior facilitators of PwMI's challenging resort-travel pursuits, confirming the practical value of the proposed motivation subdivision. The theoretical value is verified given the subdivision's significant explanatory power for resort-travel attitude and behavioral intentions, after controlling for travel purpose fulfillment. It is also feasible to achieve the targeted cultivation of self-determined motivations by supporting the basic physiological needs of autonomy, competence and relatedness. Practical implications: The study's context-based findings on the effective motivational mechanisms for PwMI can guide hospitality/tourism businesses to improve PwMI-targeted marketing effectiveness and efficiency. Originality/value: Key theoretical contributions include expanding the explanatory power of travel motivation typologies, enhanced integration of self-determination theory into travel motivation conceptualization and more accurate reflection of the widespread presence of social factors in travel motivations.